Appropriate technology, human capital and development accounting - Areendam Chanda; Beatrice Farkas (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
Over the past decade, research explaining cross country income differences has increasingly pointed to the dominant role of total factor productivity (TFP) gaps as opposed to factor accumulation. Nevertheless, it is a widely held belief that a country's ability to absorb and implement technologies is tied to its human capital. In this paper, we implement this idea in a novel specification and explore its quantitative implications within a development accounting framework. In our model, intermediate goods production takes place over a range of industries, and human capital ratios in a country influence industry specific productivities asymmetrically. As a result, in human capital abundant countries, production is concentrated around industries with high TFP, while in low human capital countries, production is concentrated around industries with low TFP. Development accounting exercises for a range of parameter values suggest that this human capital-technology complementarity may account for eighteen to twenty five percent of differences in GDP per worker which is higher than the combined direct contribution of factors of production.
Keywords: O14; O3; O47; 330; Development accounting; total factor productivity; technology-skill complementarity; appropriate technology; human capital